Reinventing identities: the gendered self in discourse - Bucholtz, Mary; Liang, A. C.; Sutton, Laurel A. (Oxford University Press, 1999)
Talk is crucial to the way our identities are constructed, altered, and defended. Feminist scholars in particular have only begun to investigate how deeply language reflects and shapes who we think we are. This volume of previously unpublished essays, the first in the new series Studies in Language and Gender, advances that effort by bringing together leading feminist scholars in the area of language and gender, including Deborah Tannen, Jennifer Coates, and Marcyliena Morgan, as well as rising younger scholars. Topics explored include African-American drag queens, gender and class on the shopping channel, and talk in the workplace.
Disponible en ligne à https://ebookcentral.proquest.com/lib/uqam/detail.action?docID=4702911 Donné en lecture au cours LIN2685, Barrett, Rusty. Indexing Polyphonous Identity in the Speech of African American Drag Queens, pp. 313-331.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; intersectionnalité; lin2685; linguistique; premier cycle; queer; ressource en ligne; sciences humaines; thématiques

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Théoriser le genre : l'héritage de Beauvoir - Jackson, Stevi (Nouvelles Questions Féministes, 1999)
En déclarant qu' "on ne naît pas femme, on le devient", Simone de Beauvoir a posé les fondements d'une conception féministe du genre. L'analyse développée dans Le Deuxième sexe a anticipé la distinction ultérieure entre sexe et genre, et a également soulevé certains problèmes liés à cette distinction. Plutôt que l'oeuvre même de Beauvoir, ce sont les discussions récentes autour de la distinction sexe/genre qui font l'objet de cet article. Plus particulièrement, j'examine la manière dont les féministes matérialistes françaises, avec qui Beauvoir elle-même a travaillé, ont fait fructifier son héritage. En affirmant que le "sexe" est un phénomène tout aussi social que le "genre", ces féministes ont maintenu une tradition anti-essentialiste fondamentalement opposée aux perspectives "différentialistes" si souvent associées à la construction anglophone du "French feminism". Je confronte la contribution de ces féministes, notamment Christine Delphy et Monique Wittig, aux conceptions féministes du genre, avec l'approche plus déconstructive associée à des théoriciennes comme Judith Butler. Ce faisant, je plaide pour une analyse matérialiste du genre et pour une vision d'un monde sans genre plutôt que d'un monde avec de multiples genres. In claiming that 'one is not born, but rather becomes, a woman', Simone de Beauvoir laid the foundations for a feminist understanding of gender. The analysis developed in The Second Sex anticipated the later distinction between sex and gender, and also evinced some of the problems associated with that distinction. It is these more recent discussions of the sex/gender distinction which are the focus of this paper, rather than Beauvoir's work itself. More specifically, I consider the ways in which French materialist feminists, with whom Beauvoir herself worked, carry forward her legacy. In arguing that ' sex' is as much a social phenomenon as 'gender', these feminists have kept alive an anti-essentialist tradition which is fundamentally opposed to the 'difference' perspectives so often associated with the anglophone construction of ' French Feminism'. I compare the contribution that these feminists, especially Christine Delphy and Monique Wittig, have made to feminist understandings of gender with the more deconstructive approach associated with thinkers such as Judith Butler. In so doing I argue the case for a materialist analysis of gender and for a vision of a world without gender rather than a world with many genders.
https://www.jstor.org/stable/40619720
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; france; féminisme matérialiste; genre; histoire; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes

Culture, society and sexuality: a reader - Parker, Richard G.; Aggleton, Peter (UCL Press, 1999)
Since the beginnings of time, people have been interested in sex - the form it takes, the pleasure it can give, the circumstances in which it occurs, and what it means - both for the individuals concerned and to society more generally. Often seen as a synonym for love, sometimes as an expression of power, and infrequently as a means of exploitation and abuse, sex is a complex and multi-faceted aspect of human behaviour that has been written about by numerous writers and theorists worldwide. This book offers an introduction to the central debates in sexuality research. Among the issues examined are the social and cultural dimensions of sex, human sexuality and sex research. It will be of use to students of sociology, cultural studies, and health and behavioural studies.
Keywords: LGBTQIA2+; VIH; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques

The good-natured feminist: Ecofeminism and the quest for democracy - Sandilands, Catriona (University of Minnesota Press, 1999)
The Good-Natured Feminist inaugure une conversation soutenue entre l'écoféminisme et les écrits récents du postmodernisme féministe et de la démocratie radicale. Partant de l'hypothèse que l'écoféminisme est un corpus de théorie démocratique, le livre raconte comment le mouvement est né des débats sur la « nature » ​​dans les féminismes radicaux nord-américains, comment il s'est ensuite mêlé à la politique identitaire et comment il cherche maintenant à inclure la nature dans la conversation démocratique et, surtout, de politiser les relations entre genre et nature dans les milieux tant théoriques qu'activistes.
http://site.ebrary.com/id/10151040
Keywords: amériques; approches et analyses; cours; environnement; fem3600; genre; identités LGBTQIA2+; militance; postmodernisme; premier cycle; ressource en ligne; régions géographiques; thématiques; écoféminisme; états-unis